Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter 4 - Inverse, Exponential, and Logarithmic Functions - 4.1 Inverse Functions - 4.1 Exercises - Page 416: 9



Work Step by Step

See: Inverse Function, p.409. Let $f$ be a one-to-one function. Then $g$ is the inverse function of $f$ if $(f\circ g)(x)=x$ for every $x$ in the domain of $g$, and $(g\circ f)(x)=x$ for every $x$ in the domain of $f$. ----------------- $f^{-1}(6)=f^{-1}[f(-3)]=f^{-1}\circ f(-3)=$ by the definition, $= -3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.